KELAS PRENATAL YOGA SEBAGAI UPAYA MENGURANGI KETIDAKNYAMANAN PADA IBU HAMIL - Windari, Kunis Lili; Ernawati, Ernawati; Nikmaturrohma, Nikmaturrohma (Politeknik Kesehatan Kemenkes malang, 2025)
Pregnant women often experience physical and psychological discomfort, particularly in the third trimester of pregnancy. Prenatal yoga has been shown to be an effective method for reducing various discomforts experienced during pregnancy, including back pain, edema, and anxiety. This community service program aims to organize prenatal yoga classes as a non-pharmacological intervention to improve the well-being of pregnant women. This activity was carried out at Community Health Center X, involving pregnant women in the second and third trimesters as participants. Evaluation was carried out using a questionnaire method before and after the intervention to measure changes in the level of discomfort. The program results show that prenatal yoga classes can significantly reduce physical and mental discomfort in pregnant women, as well as increase their readiness to face childbirth. It is hoped that this program can become an intervention model that can be widely implemented in other health facilities.